Prevalence of Metabolic Syndrome among nursing personnel and its association with occupational stress, anxiety and depression - Renata Perfeito Ribeiro; Maria Helena Palucci Marziale; Julia Trevisan Martins; Patrícia Helena Vivan Ribeiro; Maria Lucia do Carmo Cruz Robazzi; José Carlos Dalmas (Universidade de São Paulo, 2015)
OBJECTIVE: to identify the prevalence of Metabolic Syndrome among nursing personnel, and its association with occupational stress, anxiety and depression.METHOD: a descriptive correlational study undertaken with 226 nursing personnel from a teaching hospital. Data collection was undertaken through application of the Job Stress Scale, the Hospital Anxiety and Depression Scale and a sociodemographic questionnaire, with variables of Metabolic Syndrome. Univariate analyses and Chi-squared and Pearson tests were used for correlation between the variables, with a level of significance of 5%.RESULTS: 86 (38.1%) workers presented Metabolic Syndrome, of whom 183 (81.1%) were female, and 43 (19.9%) male, aged between 23 and 66 years old. In relation to anxiety and depression, 154 (68.1%) presented anxiety, with 48 (31.2%) also presenting Metabolic Syndrome; 185 (81.8%) presented depression, of whom 62 (33.5%) also had Metabolic Syndrome. It was ascertained that 61 (27.0%) workers presented stress and that of these, 14 (22.9%) presented Metabolic Syndrome.CONCLUSION: a correlation was observed between the variables of anxiety and Metabolic Syndrome and stress and Metabolic Syndrome, there being no correlation between the variables of depression and Metabolic Syndrome.